Shut up listen and do - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
This video tells you about ways to plug in to the system and how to effectiveley build your network. The way to success is to follow this system and just'shut up, listen and do
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing